1967
DOI: 10.1515/zna-1967-0115
|View full text |Cite
|
Sign up to set email alerts
|

Absolute Präzisionsbestimmung von Gitterkonstanten an Germanium- und Aluminium-Einkristallen mit Elektroneninterferenzen

Abstract: An absolute precision determination of lattice constants by electron diffraction is made with thin monocrystalline films of germanium and aluminium, having a thickness between 1000 and 5000 A. The films are prepared from the bulk material by mechanical polishing and subsequent chemical polishing or etching. The obtained values for the lattice constant α of both materials are within the accuracy Δα/α= ±3·10-5 of measurement in full agreement with the corresponding values obtained by X-ray diffraction (Smakula a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1968
1968
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Aluminum crystallizes in the space group Fm3¯m with room-temperature lattice parameter a = 4.04950(12) (Witt, 1967), that is stable up to its melting point (Hatch, 1984). According to FIZ Karlsruhe GmbH (2018) no other aluminum structure is known; however, a structural phase transition was induced by intense laser radiation (Guo et al, 2000).…”
Section: Aluminummentioning
confidence: 99%
“…Aluminum crystallizes in the space group Fm3¯m with room-temperature lattice parameter a = 4.04950(12) (Witt, 1967), that is stable up to its melting point (Hatch, 1984). According to FIZ Karlsruhe GmbH (2018) no other aluminum structure is known; however, a structural phase transition was induced by intense laser radiation (Guo et al, 2000).…”
Section: Aluminummentioning
confidence: 99%
“…(iii) It can be observed that for copper, the characteristic lengths 1 and 2 are very small in comparison with the lattice constant a, namely 1 /a = 0.1392 and 2 /a = 0.0921, whereas for aluminum it yields 1 /a = 0.2946 and 2 /a = 0.2449. The lattice constants in Table 3 have been taken from [24,51,57,58]. (iv) Moreover, if we compare the 3 characteristic lengths, we see that the value of 3 is much greater than the values of 1 and 2 reflecting the influence of the anisotropy.…”
Section: Materials Parametersmentioning
confidence: 99%
“…3 c) is indicative of a doubling of the lipid tail unit cell for the cholesterol molecules. The corresponding cholesterol Aluminum forms a face-centered cubic lattice with lattice parameter a= 4.04941Å [34].…”
mentioning
confidence: 99%